AB0201 Influence of siga on clinical activity markers in spa patients with non-radiographic and peripheral compromise. (15th June 2017) - Romero-Sanchez, C; Salas-Cuesta, F; Arias, I; Bello-Gualtero, JM; Bautista-Molano, W; Herrera, D; Castillo, D; Valle-Oñate, R
Abstract : Background: There are previous evidence about inflammatory signs related with the intestinal mucosa in spondyloarthritis patients with seronegative arthritis and them relation with articular inflammatory activity. It is uncertain the role of these serological markers on the inflammatory/clinical activity in patients with SpA Objectives: To establish the relationship among activity variables and indices, and soluble markers associated to mucosal associated lymphoid tissue in a group of SpA patients. Methods: Patients were selected by rheumatologists with the ESSG criteria. Levels of SIgA, IgA, IgA Chlamydia trachomatis, Shigella spp, Yersinia ssp, Campilobacter ssp and Salmonella ssp, CRP, ESR, HLA-B27, BASDAI, ASDAS-CRP and ASDAS-ESR were determined. A principal components analysis (PCA), Poisson Regression and multiple correspondence analysis were performed to find relationships between clinical and laboratory variables and SIgA. This study was approved for Ethics Committee. Results: 46 patients were included (78.2% males with a mean age 34.8±12.3 years). It was reported at least one gastrointestinal sing in 69.2% of patients:abdominal bloating (45%), abdominal pain (43%); all patients showed at least one musculoskeletal symptom, 69.5% enthesitis, 63% inflammatory back pain and 58.6% arthritis, as well as 43.4% previous infection and 47.8% presented HLA-B27.The PCA showed three principal factors which cover a contribution of 82.2% to explain the SIgA variation.The ASDAS-CRP, ASDAS-ESR, BASDAI variables which provide the 47.12%;the regression model shows an inverse association among SIgA and BASDAI (prevalence ratio (PR):0.43, 95% CI:0.26–0.70 p=0.001), ASDAS-CRP (PR:0.72, 95% CI:0.24–0.95 p=0.021) and ASDAS-ESR (PR:0.69, 95% CI:0.39–0.95 p=0.007); however, a risk was demonstrated among BASDAI and Yersinia IgA (PR:1.68 95% CI:1.03–2.74 p=0.036) and between ASDAS-CRP with HLA-B27 (PR:1.62 95% CI:1.18–2.19 p=0.0002). There was a relationship between the absence of clinical activity (ASDAS-CRP, ASDAS-ESR and BASDAI), previous infection, Yersinia IgA with SIgA Q1 (27.8–43.0 ug/mL); the presence of arthritis, Salmonella IgA, and high levels of CRP and ESR were related with SIgA Q2; SIgA levels among (Q3)12.2–18.0 ug/mL were associated with inflammatory back pain, obesity and Salmonella IgA <1/1600. High scores of BASDAI and ASDAS-CRP, absence of previous infection had a strong relation with low levels of SIgA. Conclusions: SIgA serum level were the only one serologic maker, which had an inverse correlation with all clinical activity variables of disease, previous infection and some specific antibodies associated with intestinal mucosal infection, suggesting a protective role of this molecular shape of IgA that is characteristic of mucosal immune responses References: Mantis NJ. Mucosal Immunol (2011) 4:603–11. Disclosure of Interest: None declared